Village Fund Management Towards Good Governance as An Effort to Realize Village Community Welfare - Dewi Sulistianingsih; Pujiono Pujiono; Arif Hidayat; Ristina Yudhanti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
Village funds are given to the village to be managed properly so that the village can provide welfare for the village community and village development. The management of village funds must be carried out gradually and carefully in its use, besides that it must be adjusted to the existing legal rules so that there is no misuse of village funds. Harjowinangun Barat Village is one of the villages in Batang Regency, where the village community still needs village funds to achieve community welfare. The village head and other village officials need to manage village funds properly following the rules and principles of good governance. The problems in this service are: (1) What are the obstacles for Harjowinangun Barat Village, Batang Regency in managing village funds? (2) How is the application of Good Governance principles in the management of Village Fund Allocation in Harjowinangun Barat Village, Batang Regency? Service activities are carried out by analyzing the problems in Harjowinangun Barat Village. After that, the team carried out a service program to realize the management of village funds following the principles of good governance. The team’s final activities were conducting discussions and forums for problem-solving around village fund management. This program aims to help government officials carry out government bureaucracy and provide assistance in managing village funds following the principles of good governance. Assistance in the transparent management of village funds for the development and development of productive economic enterprises. The West Harjowinangun BUMDes business in Batang Regency, which had been pioneered and has failed due to the pandemic, has begun to be rebuilt using village funds. In addition, the Village Fund in West Harwowinangun is planned for the construction of sports facilities.